(untitled) (Asian-Australasian Journal of Food Safety and Security, 2018)
Burger is one of the common popular fast food. The present study was carried out to isolate and characterize bacteria from burger sold in Mymensingh that could be potential threat to human health. A total of 20 burger samples (10 belonged to pre-microwave oven treated group and 10 belonged to post-microwave treated group) were collected randomly from different bakeries and fast food shops that sell burgers in Mymensingh. Isolation and identification of bacteria were carried out based on morphology, staining, cultural and biochemical tests. All the samples were found contaminated with bacteria. Total viable count (TVC), total staphylococcal count (TSC) and total coliform count (TCC) of pre-microwave oven burger samples were 7.22±0.20 log CFU/g, 6.93±0.30 log CFU/g and 3.28±0.64 log CFU/g, respectively. Similarly in post-microwave oven treated burger the TVC, TSC and TCC were 3.09±0.42 log CFU/g, 2.84±0.56 log CFU/g and 1.60±0.42 log CFU/g, respectively. Microwave heat treatment for 60 seconds markedly reduced the TVC, TSC, TCC in the burger compared to pre microwave treated group. Many of the both the pre and post-microwave oven treated burgers were found positive for Staphylococcus spp. and E. coli. The isolates of Staphylococcus were found coagulase negative and resistant to Tetracycline while sensitive to Azithromycin, Gentamycin, Kanamycin and Streptomycin. On the other hand, the isolates of E. coli were found resistant to Azithromycin and Streptomycin while sensitive to Gentamycin, Kanamycin and Tetracycline. Data of this study suggested that burgers sold in the fast-food restaurant were contaminated with antibiotic resistant Staphylococcus and E. coli that might be considered as human health hazard. Asian Australas. J. Food Saf. Secur. 2018, 2(1), 6-11